Nahmanides and Ibn Ezra's commentaries on Genesis - Jacobs, Jonathan (Journal of Jewish studies, 2019)
In this article I re-examine the question of which of Ibn Ezra's commentaries on Genesis was available to Nahmanides when he wrote his own commentary on the book. The consensus until now had been that Nahmanides was familiar with both the short commentary and the second recension. A comprehensive analysis of Nahmanides' commentary on Genesis demonstrates that this consensus is incorrect - Nahmanides was only familiar with Ibn Ezra's short commentary. This conclusion is based on our familiarity with Nahmanides' inclusive approach to his sources, as well as specific examples which prove that Nahmanides was not familiar with the second recension (and not even the 'third approach').